2022
DOI: 10.3390/ani12213049
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Citric Acid Waste for Potential Use as Animal Feed through Fermentation with Lactic Acid Bacteria and a Mixture of Fibrolytic Enzymes

Abstract: Once improperly managed, the citric acid production industry generates waste, which contributes to pollution and other environmental issues. We proposed that, with sufficient quality improvement, citric acid by-product (CAP) might be used for animal feed, thereby reducing the environmental impact. The aim of the present study was to ferment citric acid by-product (CAP) by inoculation with lactic acid bacteria (LAB) and a fibrolytic enzyme mixture for quality improvement and crude fiber reduction in the waste p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recently, several attempts have been made to successfully convert agricultural waste into biofeeds using several strains of lactic acid bacteria ( Cao et al, 2011 ; Guo et al, 2014 ; Mocanu et al, 2020 ; Tanpong et al, 2022 ). The study reported superior effects of lactobacilli inoculant ( Lactobacillus casei TH14) when used in combination with fibrolytic enzymes.…”
Section: Fermented Citrus Residue As a Nutritious Biofeedmentioning
confidence: 99%
“…Recently, several attempts have been made to successfully convert agricultural waste into biofeeds using several strains of lactic acid bacteria ( Cao et al, 2011 ; Guo et al, 2014 ; Mocanu et al, 2020 ; Tanpong et al, 2022 ). The study reported superior effects of lactobacilli inoculant ( Lactobacillus casei TH14) when used in combination with fibrolytic enzymes.…”
Section: Fermented Citrus Residue As a Nutritious Biofeedmentioning
confidence: 99%
“…Lactic acid bacteria, a common probiotic, is widely used in the food, medicine, chemical, and feed industries. [ 15 ] L. acidophilus is a parasitic probiotic in the stomach and small intestine. In addition, L. acidophilus intervention can regulate intestinal microecology, reduce blood sugar levels, and protect the digestive system.…”
Section: Introductionmentioning
confidence: 99%